Radicals and Anions of Siloles and Germoles. Issue 47 (1st June 2021) - Reinhold, Crispin R. W.; Schmidtmann, Marc; Tumanskii, Boris; Müller, Thomas
Abstract: The synthesis of persistent sila‐ and germacyclopentadienyl (silolyl‐ and germolyl‐) radicals by careful stoichiometric reduction of the corresponding halides with potassium is reported. The radicals were characterized by EPR spectroscopy and trapping reactions. The reduction of tris (trimethylsilyl)silyl‐substituted halides was successful while smaller substituents (i. e., t ‐Butyl, Ph) gave the corresponding dimers. The EPR spectroscopic parameter of the synthesized tetrolyl radicals indicate only small spin delocalization to the butadiene unit due to cross‐hyperconjugation. Silolyl‐ and germolyl anions are unavoidable byproducts and are isolated in the form of their potassium salts and characterized by X‐ray crystallography. The comparison of the molecular structures of two closely related potassium silolides provided an example for different coordination of the potassium cation to the silolyl anion (η 1 vs. η 5 coordination) that triggers the switch between delocalized and localized states. Abstract : Persistent silolyl and germolyl radicals were synthesized by reduction of sterically congested halide precursors. The radicals are pyramidalized and show only little spin delocalization.